Zakat Management at Baznas North Lombok Regency - Ernaldo Fikrul Arifin; M. Budi Utama (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze zakat management at BAZNAS North Lombok Regency, including the processes of collection, distribution, transparency, potential, local government support, and the challenges encountered. The study employed a descriptive qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. The informants consisted of leaders and administrators of BAZNAS North Lombok Regency. The findings reveal that zakat management has been implemented systematically through the collection of zakat, infaq, and sadaqah (ZIS) funds from civil servant salary deductions, Zakat Collection Units (UPZ), and transfers to official BAZNAS accounts. Zakat distribution is carried out in accordance with Islamic law to the eight categories of eligible beneficiaries (asnaf) based on field surveys. Transparency and accountability are supported by the use of the BAZNAS Management Information System (SIMBA), periodic reporting to muzakki, and weekly internal evaluations. North Lombok Regency has significant zakat potential from agriculture, trade, hospitality, and micro-enterprises. However, the optimization of this potential still faces several obstacles, including low zakat literacy, limited human resources, the community’s tendency to distribute zakat directly to beneficiaries, and limited use of digital technology. Local government support through land grants, civil servant zakat deduction policies, and regulatory support has become an important factor in strengthening the institutional capacity of BAZNAS. The study concludes that zakat management at BAZNAS North Lombok Regency has been conducted professionally, transparently, and accountably, although improvements in zakat education, human resource capacity, and service digitalization are still needed.